Using staged teaching and assessment approaches to facilitate inter-university collaboration and problem-based learning - Dawson, Henry; Davis, Gayle; Ross, Kirstin; Miller, Marie Vaganay; Tomlinson, Alastair (Frontiers in Public Health, 2024)
This article describes the segmented module design and problem-based learning approaches employed to enable parts of a higher education environmental health module (course) to be shared between universities in Wales, Northern Ireland, and Australia. The module requires students to identify the needs and assets of a community then design community-based interventions to address problems and undertake an evaluation of those interventions. Accreditation body and the degree program learning outcome requirements in the UK and Australia were found to hold many comparable knowledge, skills, and graduate attribute criteria, eliminating a potential barrier for international learning and teaching collaboration between higher education institutions. Instead, barriers to collaboration were associated with institutional issues and practicalities such as timetabling and assessment requirements. Taking a segmented approach to module design allowed staged and varied levels of collaboration between participating institutions, all delivering modules (courses) with similar learning outcomes. This provided a more sustainable environment to facilitate shared learning and teaching and fostered closer relations between programs, within these constraining factors. Students using problem-based learning and its group-working component exhibited the development of leadership, communication, and independent learning skills.